EXPLORATION OF THE EXPERIENCES OF GRADE VI STUDENTS OF SD N 1 BOGOR IN PLAYING THE GAME FREE FIRE TOWARDS THEIR ACADEMIC CAREER JOURNEY - Hanifah Az Zahra; Wahdan Najib Habiby (SOSIOEDUKASI, 2026)
This study aims to explore the experiences of sixth-grade elementary school students in playing the online game Free Fire and its relationship to learning motivation and academic career development. This study uses a qualitative approach with a phenomenological type. The research subjects consisted of students who actively play games with the support of parents and teachers. Data collection techniques included interviews, observation, questionnaires, and documentation, then analyzed using interactive analysis techniques through data reduction, data presentation, and drawing conclusions. The results show that students play primarily for entertainment and social interaction with peers, with varying intensity. Some students are able to manage their time between playing and studying, but others experience a decrease in concentration and learning motivation after playing. The impacts are not uniform, but are influenced by self-control, discipline, and supervision from parents and teachers. In general, gaming activities can provide positive or negative experiences for students' academic career development depending on time management and environmental support.